2017
DOI: 10.3389/fcimb.2017.00010
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Transcriptional Start Site Mapping and sRNA Identification in the Pathogen Leptospira interrogans

Abstract: Leptospira are emerging zoonotic pathogens transmitted from animals to humans typically through contaminated environmental sources of water and soil. Regulatory pathways of pathogenic Leptospira spp. underlying the adaptive response to different hosts and environmental conditions remains elusive. In this study, we provide the first global Transcriptional Start Site (TSS) map of a Leptospira species. RNA was obtained from the pathogen Leptospira interrogans grown at 30°C (optimal in vitro temperature) and 37°C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 60 publications
2
47
0
Order By: Relevance
“…6B). These motifs are located between 38 and 152 nucleotides upstream of the transcription start site of the perR ORF, which appears to be identical to the first nucleotide of the translation start codon (28).…”
Section: Characterization Of the Leptospira Peroxide Stress Regulatormentioning
confidence: 99%
“…6B). These motifs are located between 38 and 152 nucleotides upstream of the transcription start site of the perR ORF, which appears to be identical to the first nucleotide of the translation start codon (28).…”
Section: Characterization Of the Leptospira Peroxide Stress Regulatormentioning
confidence: 99%
“…interrogans will aid selection of the correct junction for promoter fusions to gfp (37). A 309 transcription start site was not detected for sph2 in the study, consistent with the limited 310 expression of sph2 in non-Pomona strains under standard culture conditions.…”
Section: ) 234mentioning
confidence: 57%
“…Various previous studies have documented the L. interrogans transcript (Lo et al, 2010;Pinne et al, 2012;Iraola et al, 2016). Recent investigations generated the Transcriptional Start Site (TSS) map of Leptospira species (Zhukova et al, 2017), results of which showed that a larger proportion (2,866) of the primary TSS (pTSS) were predicted in the genome of L. interrogans. Interestingly, significant numbers of the pTSSs were located within the first 10 nucleotides from the start point of translation, observations that signify translational regions of Leptospiral species that display characteristic leaderless transcripts (Zhukova et al, 2017).…”
Section: Advances On Genomics Of Leptospiramentioning
confidence: 99%
“…Recent investigations generated the Transcriptional Start Site (TSS) map of Leptospira species (Zhukova et al, 2017), results of which showed that a larger proportion (2,866) of the primary TSS (pTSS) were predicted in the genome of L. interrogans. Interestingly, significant numbers of the pTSSs were located within the first 10 nucleotides from the start point of translation, observations that signify translational regions of Leptospiral species that display characteristic leaderless transcripts (Zhukova et al, 2017). Additional studies on the L. interrogans genome sequence identified two genes (LIC11122 and LIC12287) that code for two novel proteins that were characterized and labeled as a sigma factor and a potential functional protein, respectively (Figueredo et al, 2017).…”
Section: Advances On Genomics Of Leptospiramentioning
confidence: 99%
See 1 more Smart Citation